Exploring the Praxis of Campus Management of Higher Education - Pelovello, Analiza (International Journal of Arts, Sciences and Education, 2023)
Management is at the heart of higher education. As such, practices are crucial to its meeting of educational standards. Hence, this study explored the extent of management practices along efficiency, accountability, participatory decision-making, and transparency as assessed by the student-stakeholders. Results show that management practices are observed to a very great extent. However, there remains to be a significant implication on the higher education institution’s sustainable development through its continuous observance of quality and effective management practices that cater not only to students but to all other stakeholders of the institution.